우리나라 병동 간호사의 병원 특성이 재직률, 근무기간 및 퇴직에 미치는 영향: 건강보험심사평가원(HIRAS)자료를 이용한 후향적 코호트 연구 - 서희정; 김기연; 장세진; Seo, Hee-Jung; Kim, Gi Yon; Chang, Sei-Jin (Journal of Korean Academy of Nursing, 2020)
Purpose: The purpose of this study was to investigate the effects of hospital characteristics on employment rate, working period, and retirement of ward nurses in Korea through a retrospective cohort study based on HIRAS data. Methods: Data were obtained from a report on medical care institutions of Health Insurance Review & Assessment Service (HIRAS). Data from 259,941 nurses who were working for a day or more from January 1, 2012, to December 31, 2016, at 2,942 medical care institutions were analyzed. Life table method analysis, Kaplan-Meier analysis, and Cox proportional hazard regression analysis were conducted. Results: The employment rates of 5 yeas and 10 years for the total sample were 38% and 28%, respectively. The estimated mean value of the working period was 3,642.7 days (SE: 17.4 days). Cox proportional hazard regression analyses revealed that nurses who were working at the general hospital/hospital, clinic, and nursing hospital were more likely to leave the hospital compared to those who were working at the 3rd general hospital. Nurses who were working at the medical institutions which were located in cities and countries, established by the private foundation, rated lower levels of nursing, and owned an insufficient number of beds, nurses and doctors were more likely to leave their workplace compared to those of the counterparts. Conclusion: This study indicates that hospital characteristics may play a significant role in retirement and working period of ward nurses in Korea. The improvement of hospital conditions to reduce ward nurses' retirement are needed.